What is known about population level programs designed to address gambling-related harm: rapid review of the evidence - Samantha Clune; Deepika Ratnaike; Vanessa White; Alex Donaldson; Erica Randle; Paul O'Halloran; Virginia Lewis (BMC, 2024)
Abstract Background Gambling and gambling-related harm attract significant researcher and policy attention. The liberalisation of gambling in most western countries is strongly associated with a marked rise in gambling activity and increases in gambling-related harm experienced at the population level. Programs to address gambling-related harm have traditionally focused on individuals who demonstrate problematic gambling behaviour, despite clear evidence of the effectiveness of a public health approach to high-risk activities like gambling. Little is known about the availability or efficacy of programs to address gambling-related harm at a population level. Methods The Victorian Responsible Gambling Foundation commissioned a rapid evidence review of the available evidence on programs designed to reduce gambling-related harm at a population level. The review was conducted using a public health and harm reduction lens. MEDLINE, ProQuest Central and PsychInfo databases were searched systematically. Included studies were published in English between 2017 - 2023 from all countries with gambling policy contexts and public health systems comparable to Australia's; included primary data; and focused on primary and/or secondary prevention of gambling-related harm or problems. Results One hundred and sixty-seven articles were eligible for inclusion. Themes identified in the literature included: risk and protective factors; primary prevention; secondary prevention; tertiary prevention; target population group; and public health approach. The evidence review revealed a gap in empirical evidence around effective interventions to reduce gambling-related harm at the population level, particularly from a public health perspective. Conclusions Addressing gambling-related harm requires a nuanced, multi-layered approach that acknowledges the complex social, environmental, and commercial nature of gambling and associated harms. Moreover, evidence demonstrates community programs to reduce gambling-related harm are more successful in reducing harm when based on sound theory of co-design and address the social aspects that contribute to harm.